From early micro-temporal interaction patterns to child cortisol levels: toward the role of interactive reparation and infant attachment in a longitudinal study - Müller, Mitho; Zietlow, Anna-Lena; Klauser, Nathania; Woll, Christian; Nonnenmacher, Nora; Tronick, Edward; Reck, Corinna (Frontiers in psychology, 2022)
Parental mental disorders increase the risk for insecure attachment in children. However, the quality of caregiver-infant interaction plays a key role in the development of infant attachment. Dyadic interaction is frequently investigated via global scales which are too rough to uncover micro-temporal mechanisms. Prior research found that the latency to reparation of uncoordinated dyadic states is associated with infant behavioral and neuroendocrine regulation. We investigated the hypothesis that this interactive mechanism is critical in predicting secure vs. insecure attachment quality in infancy. We also assessed the predictive quality of infant attachment regarding neuroendocrine reactivity later in childhood. A subsample of N = 58 dyads (n = 22 mothers with anxiety disorders, n = 36 controls) from a larger study were analyzed. At 3-8 months postpartum, maternal anxiety disorders were diagnosed via a structured clinical interview as well as dyadic interaction during the Face-to-Face-Still-Face (FFSF) was observed and coded on a micro-temporal scale. Infant attachment quality was assessed with the strange situation paradigm at 12-24 months of age. In an overlapping subsample of N = 39 (n = 13 mothers with anxiety disorder; n = 26 controls), we assessed child cortisol reactivity at 5 to 6 years of age. Generalized linear modeling revealed that longer latencies to interactive reparation during the reunion episode of the FFSF as well as maternal diagnosis at 3-8 months of age predict insecure attachment in children aged 12-24 months. Cox regressions demonstrated that dyads with infants who developed insecure attachment at 12-24 months of age were 48% less likely to achieve an interactive reparation at 3-8 months of age. Mixed models revealed that compared to securely attached children, children who had developed an insecure attachment at 12-24 months of age had an increased cortisol reactivity at 5 to 6 years of age during free play. The results confirm the hypothesis that the development of attachment is affected by experienced micro-temporal interactive patterns besides diagnostic categories. They also showed that infants of mothers with postpartum anxiety disorders have a more than fivefold increased risk of developing an insecure attachment than the infants of the control group. Moreover, results imply that these patterns may influence neurohormonal regulation even in preschool aged children.
Gesehen am 21.09.2022